Comparing morbidity rates between wise pattern and standard horizontal elliptical mastectomy incisions in patients undergoing immediate breast reconstruction. Issue 1 (16th November 2018) - Gunn, Jinny; Dortch, John; TerKonda, Sarvam; Schilling, Kayla; Li, Zhou; Diehl, Nancy; Gibson, Tammeza; Bagaria, Sanjay; Perdikis, Galen; McLaughlin, Sarah
Abstract: Background: Breast cancer patients with ptotic breasts pursuing mastectomy with immediate reconstruction can present challenges. A wise pattern (inverted‐T) mastectomy incision (WPM) has been suggested as an alternative to the standard horizontal elliptical mastectomy (EM) to reduce redundant skin and correct ptosis. Herein, we sought to examine the differences in morbidity between the two techniques. Methods: We performed a retrospective review of women undergoing mastectomy with immediate reconstruction at our institution from June 2007 to January 2016. We compared those undergoing WPM to a control population undergoing EM. Statistical analysis was performed evaluating clinical, pathological, and surgical outcome variables according to patient and per breast. All tests were two‐sided with alpha level set at 0.05 for statistical significance. Results: A total of 241 women underwent mastectomy and reconstruction in 421 breasts; 78/241 (32%) had WPM (149 breasts), 163/241 (68%) had EM (272 breasts). Both groups were similar in age, smoking status, diabetes, race, tumor type, and pathologic stage (all P > 0.07). Skin flap necrosis was the most frequently encountered complication, occurring in 58/149 (38.9%) of WPM breasts and in 24/272 (8.9%) of EM breasts ( P < 0.0001). There was no difference in the need for revisional procedures between the groups (WPM: 24.1% vs EM: 17.6%, P = 0.207). Conclusion: Patients should be counseled WPM is associated with higher rates of skin flap necrosis. However, this does not translate into higher rates of revisional procedures or return to OR.